Dinamika Suhu pada Sistem Tangki-Seri-Tak-Berinteraksi dengan Arus Recycle - Hermawan Yulius Deddy (Seminar Nasional Teknik Kimia Kejuangan, 2010)
This research studies the temperature dynamic behavior of non-interacting-tank (NIT) with recycle-stream which is frequently used in industries. Two tanks with volume of 25 liters are designed and arranged in series for experimentation in laboratory. Part of liquid from Tank-2 is recycled back to the Tank-1. In this work, the liquid volume of both Tank-1 and Tank-2 are remained at constant value. The heat disturbance load has been made based on both step increase and decrease. Those disturbances include the changes of temperature in input (T i) and recycle (TR) streams. The temperature dynamic behavior of NIT system has also been explored. As can be seen from our investigation in laboratory, both of Tank-1 and Tank-2 in NIT system produce a stable response to the disturbance change in temperature of the input and recycle streams. Furthermore, dynamic simulation using computer programming is also done, and its simulation results are compared with the experiment data from laboratory. The developed mathematical model of the NIT system is solved numerically. Such mathematical model is rigorously examined in Scilab software environment. This research also shows that the trends of temperature dynamic simulation results are quite similar with those in our experiment results.